Switching From Proximal to Distal Radial Artery Access for Coronary Chronic Total Occlusion Recanalization - Achim, Alexandru; Szigethy, Tímea; Olajos, Dorottya; Molnár, Levente; Papp, Roland; Bárczi, György; Kákonyi, Kornél; Édes, István F.; Becker, Dávid; Merkely, Béla; Van den Eynde, Jef; Ruzsa, Zoltán (Frontiers in Cardiovascular Medicine, 2022)
Background Distal radial access (DRA) was recently introduced in the hopes of improving patient comfort by allowing the hand to rest in a more ergonomic position throughout percutaneous coronary interventions (PCI), and potentially to further reduce the rate of complications (mainly radial artery occlusion,[RAO]). Its safety and feasibility in chronic total occlusion (CTO) PCI have not been thoroughly explored, although the role of DRA could be even more valuable in these procedures. Methods From 2016 to 2021, all patients who underwent CTO PCI in 3 Hungarian centers were included, divided into 2 groups: one receiving proximal radial access (PRA) and another DRA. The primary endpoints were the procedural and clinical success and vascular access-related complications. The secondary endpoints were major adverse cardiac and cerebrovascular events (MACCE) and procedural characteristics (volume of contrast, fluoroscopy time, radiation dose, procedure time, hospitalization time). Results A total of 337 consecutive patients (mean age 64.6±9.92 years, 72.4% male) were enrolled (PRA=257, DRA=80). When compared with DRA, the PRA group had a higher prevalence of smoking (53.8% vs 25.7%, SMD=0.643), family history of cardiovascular disease (35.0% vs 15.2%, SMD=0.553), and dyslipidemia (95.0% vs 72.8%, SMD=0.500). The complexity of the CTOs was slightly higher in the DRA group, with higher degrees of calcification and tortuosity (both SMD >0.250), more bifurcation lesions (45.0% vs 13.2%, SMD = 0.938), more blunt entries (67.5% vs 47.1%, SMD = 0.409). Contrast volumes (median 120 ml vs 146 ml, p=0.045) and dose area product (median 928 mGy×cm² vs 1300 mGy×cm², p<0.001) were lower in the DRA group. Numerically, local vascular complications were more common in the PRA group, although these did not meet statistical significance (RAO: 2.72% vs 1.25%, p=0.450; large hematoma: 0.72% vs 0%, p=1.000). The procedural and clinical success rates were comparable through DRA vs PRA (p=0.6), moreover, the 12-months rate of MACCE was similar across the 2 groups (9.09% vs 18.2%, p=0.35). Conclusion Using DRA for complex CTO interventions is safe, feasible, lowers radiation dose and makes dual radial access more achievable. At the same time, there was no signal of increased risk of periprocedural or long-term adverse outcomes.